Acute Myopericarditis after COVID-19 Vaccine in Teenagers - Shashikanth Ambati; Michael Colon; Maya Mihic; Javier Sanchez; Adnan Bakar (Case Reports in Cardiology)
Background. There have been an increasing number of reports of myocarditis and pericarditis in adolescents and young adults after coronavirus disease 19 vaccinations. The pathophysiology of myocarditis after this vaccination is indeterminate currently. The problem is a relatively new phenomenon, and so there are no current guidelines on how to manage these cases of myopericarditis. We intend to describe our management in these two cases so that it can help guide pediatricians, intensivists, and cardiologists taking care of similar cases. Case Summaries. The first case is a young adolescent who presented with chest pain after receiving his second dose of coronavirus disease 19 vaccination with no other symptoms. His troponin was found to be 40 ng/mL. He had a normal echocardiogram and chest CT angiogram. His troponins trended down with symptomatic pain management after 3 days. The second case is another adolescent who presented with fever, fatigue, headache, and chest pain 3 days after receiving his second dose of coronavirus vaccine. His troponin was elevated to 5 ng/mL, electrocardiogram with ST segment elevations, and mildly decreased systolic function on echocardiogram. His troponins and electrocardiogram were normalized in 3 days at the time of his discharge. Conclusion. The clinical course of vaccine-associated myocarditis appears favorable as both our patients have responded well to medications and rest with prompt improvement in symptoms with full recovery. The experience remains limited at this time regarding the investigations, management, and follow-up of this novel clinical entity. It is vital for all the health care providers taking care of adolescents to have knowledge about this phenomenon and make correct diagnosis in those presenting with chest pain after COVID-19 vaccine and in preventing unnecessary invasive procedures such as coronary angiogram to rule out acute coronary syndromes.